Cancer vaccination with telomerase peptide GV1001 - Kyte, Jon Amund (Expert opinion on investigational drugs, 2009)
Telomerase is highly expressed in essentially all cancer forms, while the expression in normal tissues is restricted. Moreover, telomerase activity is considered indispensable for tumor immortalization and growth. Human telomerase reverse transcriptase (hTERT), the rate-limiting subunit of the telomerase complex, is therefore an attractive target for cancer vaccination. The present review provides an update on the development of GV1001, a peptide vaccine representing a 16-aa hTERT sequence. GV1001 binds multiple HLA class II molecules and harbors putative HLA class I epitopes. The peptide may therefore elicit combined CD4/CD8 T-cell responses, considered important to initiate tumor eradication and long-term memory. Phase I/II trials in advanced pancreatic and pulmonary cancer patients have demonstrated GV1001-specific T-cell responses in > 50% of subjects, without clinically important toxicity. The results indicate a correlation between development of GV1001-specific responses and prolonged survival. However, as in most cancer vaccine trials, a large proportion of immune responders experience no clinical benefit. Long-term survivors harbor durable GV1001-specific T-cell responses with high IFN-gamma/IL-10 ratios and polyfunctional cytokine patterns. Interestingly, the cytokine profiles do not follow a T(H)1/T(H)2 delineation. Here, the author discusses how immunomonitoring may be improved to discriminate between efficient and pointless immune responses, and which questions to address in the further development of GV1001.